Breast Cancer Screening in Low-Income Countries: A New Program for Downstaging Breast Cancer in Tanzania. (5th April 2022) - Cherlin, Darcy S.; Mwaiselage, Julius; Msami, Khadija; Heisler, Zoe; Young, Heather; Cui, Xingwei; Soliman, Amr S.
Abstract : Background. Most breast cancer diagnoses in Tanzania are in advanced stages. The Ocean Road Cancer Institute (ORCI) established a new breast cancer screening program in 2014 to reduce advanced-stage diagnoses. This study is aimed at describing the screening program's referral process and at identifying patient and health system factors that contribute to patients completing diagnostic testing referrals. Methods . Six-hundred and forty patients were included in the study. Testing types, outcomes, and date of diagnostic results were abstracted from records at ORCI and Muhimbili National Hospital (MNH) to determine the proportion of testing completed and the duration between initial referrals and diagnostic tests. Prediction of completion of diagnostic testing was investigated in logistic regression. Results . Of the patients who received referrals for further testing, fifty-two percent completed the recommended ultrasound (USS), mammography (MMG), and fine-needle aspiration cytology (FNAC). Only 33.0% of patients completed the recommended MMG referrals compared to 55.0% for ultrasound and 68.7% for FNAC. The average number of days between initial screening and results was 42 days for MMG, 20 days for USS, and 18 days for FNAC. Significant predictors for completing referrals for USS, FNAC, and MMG included age < 44 and >55 years, presenting with symptoms at the initial appointment, and education. The odds of completing an USS was 3.03 (95% CI, 1.65-5.64) for patients 25–34, 2.27 (95% CI, 1.17-4.48) for patients 35–44, and 4.41 (95% CI, 1.66-10.11) for patients older than 55 years compared to the reference group (age 19–24). The presence of symptoms at the initial appointment was a significant predictor of FNAC. The odds of completing an FNAC was 1.55 (95% CI, 1.02-3.72) for symptomatic compared to nonsymptomatic patients. Education was a significant predictor of MMG. The odds of receiving MMG was 4.29 (95% CI, 1.05-21.00) for patients with tertiary education or higher compared to primary education or lower. Possession of health insurance for treatment and living in Dar es Salaam were not significant predictors. Discussion. Future research should focus on patients' understanding of recommended referrals and factors that influence decision-making. Investigating the cost effectiveness of scaling up screening programs and setting up a patient navigation program that follow patients as they complete the recommended treatment plan will be crucial for Tanzania and other developing countries as they seek to launch and strengthen screening programs.